PERHITUNGAN NILAI KAYU HUTAN RAKYAT DI KABUPATEN PADANG PARIAMAN DENGAN MENGGUNAKAN PENGINDERAAN JAUH (Wood Value on Forest Community in Padang Pariaman District Using Remote Sensing): Aisyah Amini dan Ahyuni - Journal, Administrator (Jurnal Hutan Tropika, 2018)
ABSTRACTThis study aims to determine the canopy density in the community forests of Padang PariamanRegency and the value of community forest timber based on the volume of wood. This type ofresearch is quantitative descriptive using the remote sensing method. The population in this studyis the community forest area in Padang Pariaman Regency based on six land cover classes, withtree sampling to obtain stand potential data by making circular sample plots in each land coverclass. The results of this study indicate that the level of vegetation density in the study area variesfrom very tight, tight, quite tight, not tight, and there is no vegetation. For the most dominatingcategory is the tight category with an area of 57,442.08 ha (74.82%). The total value of wood inthe study area of 16 species of trees with a total volume of 953 m3 / ha amounting toRp18,942,687,097,586 (eighteen trillion, nine hundred forty two billion, six hundred eighty sevenmillion, ninety-seven thousand five hundred eighty-six).Keywords: Community forest, vegetation density,value of wood